ACCELERATORS FOR STARTUPS IN EUROPE - Serwatka, Anna (Copernican Journal of Finance & Accounting, 2018)
According to Steve Blank, a startup is a temporary organization that is looking for a profitable, scalable, and repeatable business model. The aim of this article is to compare the startup environments in Poland and other European Union countries, in particular the functioning of accelerators and incubators. The study is based on analysing the sources of acceleration programs and methods of supporting young companies. It turns out that since 2007, the economies of European countries and the US have been feeling the growth of small enterprises that are innovative, and their products are often revolutionizing global markets. Many startups also end up in bankruptcy, but this does not discourage entrepreneurs from creating more and more new teams work on new innovative technologies. One of the biggest problems for start-up companies is finding financing. Hence the interest in the acceleration programs, thanks to which companies gain financing and, above all, mentoring and contact with investors and customers. The effects of cooperation between accelerators and young companies can also be seen on the Polish market. In the last two years new government projects have been created and directed by large corporations, which are supporting the ideas of young people and encourage the development of startups.